Bacteriophage Therapy to Control Bovine Mastitis: A Review - Janet Y. Nale; Neil R. McEwan (MDPI AG, 2023)
Bovine mastitis is a polymicrobial disease characterised by inflammation of the udders of dairy and beef cattle. The infection has huge implications to health and welfare of animals, impacting milk and beef production and costing up to EUR 32 billion annually to the dairy industry, globally. Bacterial communities associated with the disease include representative species from Staphylococcus, Streptococcus, Enterococcus, Actinomyces, Aerococcus, Escherichia, Klebsiella and Proteus. Conventional treatment relies on antibiotics, but antimicrobial resistance, declining antibiotic innovations and biofilm production negatively impact therapeutic efficacy. Bacteriophages (phages) are viruses which effectively target and lyse bacteria with extreme specificity and can be a valuable supplement or replacement to antibiotics for bovine mastitis. In this review, we provide an overview of the etiology of bovine mastitis, the advantages of phage therapy over chemical antibiotics for the strains and research work conducted in the area in various model systems to support phage deployment in the dairy industry. We emphasise work on phage isolation procedures from samples obtained from mastitic and non-mastitic sources, characterisation and efficacy testing of single and multiple phages as standalone treatments or adjuncts to probiotics in various in vitro, ex vivo and in vivo bovine mastitis infection models. Furthermore, we highlight the areas where improvements can be made with focus on phage cocktail optimisation, formulation, and genetic engineering to improve delivery, stability, efficacy, and safety in cattle. Phage therapy is becoming more attractive in clinical medicine and agriculture and thus, could mitigate the impending catastrophe of antimicrobial resistance in the dairy sector.